Effects of prolonged hypoxia and bed rest on appetite and appetite-related hormones. (1st December 2016) - Debevec, Tadej; Simpson, Elizabeth J.; Mekjavic, Igor B.; Eiken, Ola; Macdonald, Ian A.
Abstract: Environmental hypoxia and inactivity have both been shown to modulate appetite. To elucidate the independent and combined effects of hypoxia and bed rest-induced inactivity on appetite-related hormones and subjective appetite, eleven healthy, non-obese males underwent three experimental interventions in a cross-over and randomized fashion: 1) Hypoxic confinement combined with daily moderate-intensity exercise (HAMB, Fi O2  = 0.141 ± 0.004; Pi O2  = 90.0 ± 0.4 mmHg) 2) Bed rest in normoxia (NBR, Fi O2  = 0.209; Pi O2  = 133.1 ± 0.3 mmHg) and 3) Bed rest in hypoxia (HBR, Fi O2  = 0.141 ± 0.004; Pi O2  = 90.0 ± 0.4 mmHg). A mixed-meal tolerance test (MTT), followed by an ad libitum meal were performed before (Pre) and after 16-days (Post) of each intervention. Composite satiety scores (CSS) during the MTT were calculated from visual analogue scores, while fasting and postprandial concentrations of total ghrelin, peptide YY (PYY), glucagon-like peptide-1 (GLP-1) and leptin were quantified from arterialized-venous samples. Postprandial CSS were significantly lower at Post compared to Pre in NBR only (P < 0.05) with no differences observed in ad libitum meal intakes. Postprandial concentrations and incremental area under the curve (AUC) for total ghrelin and PYY were unchanged following all interventions. Postprandial GLP-1 concentrations were only reduced at Post following HBR (P < 0.05) with resulting AUC changes being significantly lower compared to HAMB (P < 0.01). Fasting leptin was reduced following HAMB (P < 0.05) with no changes observed following NBR and HBR. These findings suggest that independently, 16-day of simulated altitude exposure (∼4000 m) and bed rest-induced inactivity do not significantly alter subjective appetite or ad libitum intakes. The measured appetite-related hormones following both HAMB and HBR point to a situation of hypoxia-induced appetite stimulation, although this did not reflect in higher ad libitum intakes. Clinical Trial Registration Number: NCT02293772 .